Absenteeism prevention in preschools in Chile: Impact from a quasi-experimental evaluation of 2011–2017 Ministry of Education data - Arbour, MaryCatherine; Soto, Carolina; Alée, Yanira; Atwood, Sidney; Muñoz, Pablo; Marzolo, Marcela (Frontiers in Education, 2023)
In 2007, to promote social equity, Chile expanded coverage and subsidies for early childhood education (ECE). Fundación Educacional Oportunidad (OFE) aimed to improve ECE quality through its professional development program for teachers and school leaders, Un Buen Comienzo (UBC). An experimental evaluation showed that high levels of absenteeism moderated UBC’s impact: despite moderate to large positive impacts on preschool quality, only children who attended most frequently experienced positive impacts on targeted language and literacy skills. In 2012, OFE began prioritizing attendance promotion and chronic absenteeism prevention. Using a Breakthrough Series Collaborative (BTS) that combines continuous quality improvement methods and networked peer learning, OFE tested a theory of change and several innovations, including Absenteeism Committees comprised of school teams and families; a new real-time data platform; and a set of universal and targeted strategies to apply with families at risk for chronic absenteeism. In 2014-2015, OFE expanded the UBC program to nineteen schools in Chile’s VI Region, five of which prioritized attendance promotion. This study describes the intervention strategies and BTS implementation approach, and we use publicly available Ministry of Education databases to analyze rates of absences and chronic absenteeism in public preschools in Chile’s VI region from 2011 to 2017 (n=1218 children per year; 63,689 child-months of data), comparing rates between UBC schools that prioritized attendance (n=5), UBC schools that did not prioritize attendance (n=14), and non-UBC schools (n=27). Children missed, on average, 14.0%–14.4% of schooldays. Rates of chronic absenteeism were 50.9%–54.2%. Statistical Process Control charts show an initial increase in the percentage of days absent per child each month (13.4% to 16.3%) in UBC Schools prioritizing attendance, followed by a decrease to 12.9%. The percentage of children with chronic absenteeism decreased from 54.2% to 35%. Interrupted time series analyses suggest that these reductions can be attributed to UBC participation. This study 1) replicates findings from prior research indicating that absenteeism rates are sufficiently high among Chilean preschoolers to diminish ECE’s potential benefits, and 2) demonstrates the effectiveness of multi-level strategies implemented using continuous improvement methods and networked peer learning to promote attendance and reduce chronic absenteeism.